3D differential interference contrast microscopy using polarisation‐sensitive tomographic diffraction microscopy. (30th November 2022) - Verrier, Nicolas; Taddese, Asemare Mengistie; Abbessi, Riadh; Debailleul, Matthieu; Haeberlé, Olivier
Summary: Tomographic diffraction microscopy (TDM) is a generalisation of digital holographic microscopy (DHM), for which the illumination angle onto the sample is fully controlled, which has become a tool of choice for 3D, high‐resolution imaging of unlabelled samples. TDM makes it possible to obtain the optical field in both amplitude and phase for each illumination angle. Proper information reallocation eventually allows for 3D reconstruction of the complex refractive index map. On the other hand, polarisation array sensors (PAS) paves new way for TDM, as vectorial information assessment about the investigated sample. In this contribution, we show an alternative use of this polarisation information based on the phase sensitive nature of TDM. Here, we demonstrated that TDM coupled with PAS can lead to a 3D differential interference contrast (DIC) microscope with almost no experimental configuration modification.